Manajemen dan Kebijakan Politik Pemerintahan di Indonesia tentang Pendidikan Agama Islam - Halimah, Siti (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2015)
The paper highlights Islamic education in Indonesia that can be classified intothree kinds. First, Islamic education as an institution with Islamic educationrecognized by the government. Second, Islamic education as a subject givenfrom elementary school to college level. Third, Islamic education as a valuein the national education system. When Islam came to Indonesia, it directlyand indirectly has been in contact with the government or the policy of theIndonesian authorities. This more or less already affects the growth, developmentand advancement of Islamic education in Indonesia. The culmination of thegovernment’s acknowledgment of the existence of Islamic education is Law No.20 Year 2003 on National Education System, which regulates the implementationof a national education system as desired by the 1945 Constitution that integratesIslamic education into the national education system.Key words: Management, Politics, government, PAI